Beneficial Effects of n-3 Fatty Acids on Cardiometabolic and Inflammatory Markers in Type 2 Diabetes Mellitus: A Clinical Trial - Mazaherioun, Maryam (Med Princ Pract, 2018)
OBJECTIVE: To determine the effect of supplementation with n-3 polyunsaturated fatty acids (PUFAs) on circulatory resistin and monocyte chemoattractant protein 1 (MCP-1) levels in type 2 diabetes mellitus (T2DM) patients. SUBJECTS AND METHODS: This was a 10-week, placebo-controlled, double-blind, randomized trial of n-3 PUFAs (2,700 mg/day) versus placebo (soft gels containing 900 mg of edible paraffin). Forty-four T2DM patients were supplemented with n-3 PUFAs and another 44 patients received placebo (3 patients discontinued the trial). Serum resistin, MCP-1, and the lipid profile were measured before and after supplementation. The adiponectin-resistin index (1 + log(10) [resistin] – log(10) [adiponectin]) and atherogenic index (log(10) triglyceride/high-density lipoprotein cholesterol) of plasma (an indicator of cardiovascular complications) were assessed. The independent Student t test was used to assess the differences between the supplement and placebo groups and the paired t test to analyze the before/after changes. RESULTS: In this study, n-3 PUFAs reduced serum MCP-1 levels (from 260.5 to 230.5 pg/mL; p = 0.002), but they remained unchanged in the placebo group. n-3 PUFAs could not decrease serum resistin levels. The adiponectin-resistin index was significantly reduced after supplementation with n-3 PUFAs when compared to the placebo. The atherogenic index was also significantly improved after supplementation with n-3 PUFAs (from 1.459 to 1.412; p = 0.006). CONCLUSIONS: The MCP-1 levels and lipid profile were improved after supplementation with n-3 PUFAs, but resistin serum levels were not changed. Hence, the anti-inflammatory effects of n-3 PUFAs might be mediated by targeting MCP-1.